Analgesic effects of alcohol in adults with chronic jaw pain. (22nd August 2022) - Vitus, Darya; Williams, Michelle K.; Rizk, Mehdi; Neubert, John K.; Robinson, Michael; Boissoneault, Jeff
Abstract: Background: Although recent literature provides promising support for the analgesic properties of alcohol, potential differences in alcohol analgesia as a function of chronic pain status are not well understood. Thus, this study examined chronic pain status as a potential moderator of alcohol analgesia and distinguished between multiple aspects of pain experience and sensitivity: pain threshold, pain intensity, pain unpleasantness, and perceived relief. Methods: Social drinkers with ( N = 19) and without ( N = 29) chronic jaw pain completed two testing sessions in a counterbalanced order: alcohol (target BrAC = 0.08 g/dl) and placebo. In each, pressure algometry was performed at the insertion of the masseter. Alcohol analgesia was assessed by examining the main and interactive effects of beverage condition, pressure level (4, 5, or 6 pound‐feet [lbf]), and chronic jaw pain status (chronic pain vs. pain‐free control) on quantitative sensory testing measures and pain relief ratings following noxious stimuli. Results: Analyses indicated significant increases in pain threshold and pain relief and reductions in pain unpleasantness and pain intensity, under the alcohol condition. Chronic pain participants demonstrated lower pain thresholds and greater pain intensity and pain unpleasantness ratings than controls. There were no interactive effects of alcohol and pain conditions on any pain measure. Conclusions: Findings provide experimental evidence of alcohol's analgesic and pain‐relieving effects and suggest that these effects do not significantly differ by chronic pain status. Individuals, who self‐medicate pain via alcohol consumption, irrespective of pain status, may be at increased risk to engage in hazardous drinking patterns and thus experience adverse alcohol‐related consequences. Abstract : Although acute alcohol intake appears to have analgesic effects, potential differences as a function of chronic pain status are not well understood. Thus, this study examined chronic pain status as a potential moderator of alcohol analgesia and distinguished between multiple aspects of pain experience and sensitivity: pain threshold, pain intensity, pain unpleasantness, and perceived relief. Findings provide further experimental evidence of alcohol's analgesic and pain‐relieving effects, but suggest these effects do not significantly differ by chronic pain status.